2011
DOI: 10.3174/ajnr.a2592
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 2-Year Angiographic Outcomes of Stent- and Nonstent-Assisted Coil Embolization in Unruptured Aneurysms with an Unfavorable Configuration for Coiling

Abstract: BACKGROUND AND PURPOSE:Stents are known to have hemodynamic and biologic effects in addition to their mechanical scaffold effect. To determine whether stents affect long-term outcomes after coiling of unruptured aneurysms, we compared angiographic outcomes at 2 years postembolization for stent-and nonstent-assisted coiled unruptured aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 16 publications
2
50
0
Order By: Relevance
“…There was no difference in the rate of recanalization between the stent-assisted (17.5%) and non-stent-assisted coil groups (21%, p = 0.895). 12 In a commentary on the report by Piotin et al 23 addressing general concerns about stenting aneurysms, Raymond and Darsaut 26 concluded that no credible data support the use of stents and that randomized trials are sorely needed.…”
Section: Evolution Of Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no difference in the rate of recanalization between the stent-assisted (17.5%) and non-stent-assisted coil groups (21%, p = 0.895). 12 In a commentary on the report by Piotin et al 23 addressing general concerns about stenting aneurysms, Raymond and Darsaut 26 concluded that no credible data support the use of stents and that randomized trials are sorely needed.…”
Section: Evolution Of Treatmentmentioning
confidence: 99%
“…In the group with repeat imaging, 145 patients (24.3%) had mi- nor postcoiling residuals and 127 (22.1%) had significant aneurysm residual or growth. In the latter group, initial treatment with coiling resulted in complete occlusion in 68.5% (87), subtotal occlusion in 22.0% (28), and incomplete occlusion in 9.4% (12). The fact that the 68.5% of the patients with significant aneurysm residual or growth on follow-up were documented to have had complete aneurysm obliteration after initial treatment is troublesome and emphasizes the risk of recurrence of coil-treated aneurysms and the need for continued follow-up.…”
Section: Obliteration and Rebleeding Of Aneurysmsmentioning
confidence: 99%
“…In a single-center series comparing outcomes for aneurysms treated with and without adjunctive stent placement, angiographic recanalization rates at an average time of 15 months were lower in the stented group (8.1%) compared with the nonstented group (37.5%; P Ͻ .001). 47 Another single-center study found no significant difference in recurrence rates between patients coiled with adjunctive stent placement and those coiled without stent placement, 48 which may have been due to achievement of similar high packing attenuation by using the double-microcatheter technique and balloon remodeling in the patients not treated with stent placement. Stent placement might offer an indirect mechanism of reducing aneurysm recurrence by allowing greater packing attenuation.…”
Section: Stent-assisted Coil Embolizationmentioning
confidence: 99%
“…Greater packing helps to avoid coil compaction 10) and diminishes the intra-aneurysmal blood flow velocity and wall shear stress, 11) even in cases with stent assistance. 8) Use of stents reduced the risk of coil protrusion to the parent vessel, but restricted the movement of the microcatheter. In cases where microcatheter movement is restricted, it is important to understand the role of the coil's shape memory and the stiffness of the coil on coil distribution.…”
Section: Introductionmentioning
confidence: 99%
“…2,3) Recurrence following coil embolization is likely related to the packing density of coils within the aneurysm, as low coil packing density is associated with an increased risk of aneurysm recurrence. [4][5][6][7] Despite the improvements in coil embolization techniques, including stent-assisted coil embolization, coil embolization for wide-necked 8) and bilobulated aneurysms 9) remains technically challenging. Greater packing helps to avoid coil compaction 10) and diminishes the intra-aneurysmal blood flow velocity and wall shear stress, 11) even in cases with stent assistance.…”
Section: Introductionmentioning
confidence: 99%